Introducing a New Intrinsic Metric - Rainio Oona; Vuorinen Matti (SPRINGER BASEL AG, 2022)
A new intrinsic metric called the t-metric is introduced. Several sharp inequalities between this metric and the most common hyperbolic type metrics are proven for various domains G subset of R-n. The behaviour of the new metric is also studied under a few examples of conformal and quasiconformal mappings, and the differences between the balls drawn with all the metrics considered are compared by both computational and analytical means.